RNO 54: A Previously Unappreciated FU Ori Star - Lynne A. Hillenbrand; Adolfo Carvalho; Jan van Roestel; Kishalay De (The Astrophysical Journal Letters, 2023)
We present evidence in support of the hypothesis that the young stellar object RNO 54 is a mature-stage FU Ori type source. The star was first cataloged as a “red nebulous object” in the 1980s but appears to have undergone its outburst prior to the 1890s. Present-day optical and near-infrared spectra are consistent with those of other FU Ori-type stars, both in the details of spectral line presence and shape, and in the overall change in spectral type from an FGK-type in the optical, to the M-type presented in the near-infrared. In addition, the spectral energy distribution of RNO 54 is well-fit by a pure-accretion disk model with parameters: $\dot{M}={10}^{-3.45± 0.06}$ M _⊙ yr ^−1 , M _* = 0.23 ± 0.06 M _⊙ , and R _inner = 3.68 ± 0.76 R _⊙ , though we believe R _inner is likely close to its upper range of 4.5 R _⊙ in order to produce a ${T}_{\max }=7000$ K that is consistent with the optical to near-infrared spectra. The resulting L _acc is ∼265 L _⊙ . To find these values, we adopted a source distance d = 1400 pc and extinction A _V = 3.9 mag, along with disk inclination i = 50 deg based on the consideration of confidence intervals from our initial disk model, and in agreement with observational constraints. The new appreciation of a well-known source as an FU Ori-type object suggests that other such examples may be lurking in extant samples.